Influence of Neuropsychological Development of Children on Their Verbal Abilities - Oshchepkova, E; Zubova, E (KnE Life Sciences, 2018)
Learning disabilities in childhood are often caused by certain delays in language and higher mental functions development. So nowadays comprehensive research of child language development and its neuropsychological base is of great demand. The objective of the present study was to discover relationships between children’s age, certain characteristics of speech production, neuropsychological and neurolinguistic development. 126 students (51 first-graders and 75 second-graders) were recruited. They underwent complete neuropsychological assessment along with the trial “Creating a Story based on the series of pictures”. The results show that age is an important factor of neuropsychological development from the first to second grade. It concerns especially frontal lobe development. Neuropsychological development also correlates with neurolinguistical level: children who are better at programming and control, analytic and holistic strategies would be more successful in the trial “Creating a Story based on the series of pictures”, their speech would be more correct lexically as well as grammatically and syntactically. We also show that speech particularities and their correlation with neuropsychological indexes would vary in first- and second grades. Keywords: Lurian neuropsychology; child neuropsychology; neurolinguistics; neuropsychological development; Creating a Story based on the series of pictures; speech.